Characterization of Biochar and Syngas Obtained from Pellets of Grape Vine and Sun Flower Husk Using A Pyrolysis System. (10th June 2016) - Sorgonà, A.; Longo, L.; Proto, A.R.; Cavalletti, P.; Cecchini, M.; Salvati, L.; Gallucci, F.; Colantoni, A.
Abstract: Biochar produced from pellet obtained from grapevine (GV) and sunflower husk (SFH) at different temperature (400 and 500 °C) were studied by pyrolysis batch reactor. Chemical and physical evolution of biomass under pyrolysis conditions was determined and products characterization was evaluated, including main organic components in gaseous stream. The Biochar is a "porous carbonaceous solid" produced by thermochemical conversion of organic materials in an oxygen depleted atmosphere, which has physiochemical properties suitable for the safe and long-term storage of carbon in the environment and, potentially, soil improvement. Results have shown a decrease in yield as an increase in temperature. The objective of this work is to improve the acknowledgment for the alternative use of the biochar gained from agro-forestry biomass residuals grapevine and sunflower husks by means of modern chemical and physical characterization tools.